Menggali Akar Pendidikan : Memahami Perenialisme Dan Esensialisme Dalam Filsafat Pendidikan - Dewi Khalwatus Salwa; Fiqrotul Azizah; Salwa Zahrah Safiyah; M. Yunus Abu Bakar (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
Education in the era of globalization faces rapid social, cultural, and technological changes. Labor-market demands and scientific development encourage schools to adjust their curricula to emphasize short-term practical skills. As a result, philosophical, moral, and character-building dimensions are often neglected. In the tradition of educational philosophy, perennialism and essentialism offer frameworks for restoring education to its fundamental goals. Perennialism emphasizes universal values, rationality, and great works as foundations for intellectual and moral formation. Essentialism focuses on core knowledge, academic discipline, and social responsibility as the basis for shaping effective individuals. Exploring these two schools is important for balancing modern demands with fundamental values. Education grounded in strong philosophical principles can foster academic competence, social skills, moral integrity, and cultural awareness. Therefore, a deep understanding of perennialism and essentialism is relevant for building an educational system that is resilient and meaningful. These traditions also guide institutions in designing curricula that not only meet economic needs but also shape whole human beings. By balancing modern skill demands with enduring values, education becomes a medium capable of preserving cultural identity, nurturing critical thinking, and preparing learners to face global dynamics wisely. This makes education a strategic force in building a strong and sustainable civilization.